Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

The bibliometric analysis and review of dioxin in waste incineration and steel sintering - Yi Xing; Hui Zhang; Wei Su; Qunhui Wang; Haibin Yu; Jiaqing Wang; Rui Li; Changqing Cai; Zhiliang Ma (Environmental Science and Pollution Research, 2019)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Two new polyketides isolated from a diethyl sulphate mutant of marine-derived Penicillium purpurogenum G59 - Chang-Jing Wu; Hua Qiao; Cheng-Bin Cui; Yu Yang; Rui Xu; Chun-Xiao Sun; De-Hai Li; Chang-Wei Li (Natural Product Research, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Investigating the urbanization process and its impact on vegetation change and urban heat island in Wuhan, China - Xuan Gui; Lunche Wang; Rui Yao; Deqing Yu; Chang’an Li (Environmental Science and Pollution Research, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

De Novo Assembled Transcriptome Analysis and Identification of Genic SSR Markers in Red-Flowered Strawberry - Yan Ding; Li Xue; Rui-xue Guo; Gang-jun Luo; Yu-tong Song; Jia-jun Lei (Biochemical Genetics, 2019)

Transcriptional regulation contributes more to Monascus pigments diversity in different strains than to DNA sequence variation - Xiaoyu Guo; Yao Li; Rui Zhang; Jiyuan Yu; Xinbao Ma; Mianhua Chen; Yurong Wang (World Journal of Microbiology and Biotechnology, 2019)

Crystal structure of norsethite-type BaMn(CO3)2 and its pressure-induced transition investigated by Raman spectroscopy - Wen Liang; Lin Li; Yuan Yin; Rui Li; Zeming Li; Xiqiang Liu; Chaoshuai Zhao; Shuguang Yang; Yong Meng; Zengsheng Li; Yu He; Heping Li (Physics and Chemistry of Minerals, 2019)

Importance of thermal adaptation of Amphobotrys ricini in its infection of Asian copperleaf (Acalypha australis) - Lin Yu; Rui Zhang; Xue Li; Guoqing Li; Jing Zhang (Journal of General Plant Pathology, 2019)

ABA signaling rather than ABA metabolism is involved in trehalose-induced drought tolerance in tomato plants - Wenqing Yu; Ruirui Zhao; Liu Wang; Shujuan Zhang; Rui Li; Jiping Sheng; Lin Shen (Planta, 2019)

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Targeted Gene Disruption in Pacific Oyster Based on CRISPR/Cas9 Ribonucleoprotein Complexes - Hong Yu; Huijuan Li; Qi Li; Rui Xu; Chenyang Yue; Shaojun Du (Marine Biotechnology, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Quaternary phosphonium cationic ionic liquid/porous metal–organic framework as an efficient catalytic system for cycloaddition of carbon dioxide into cyclic carbonates - Yu Lin Hu; Rui Li Zhang; Dong Fang (Environmental Chemistry Letters, 2019)

A reliable non-invasive PCR method for takin (Budorcas taxicolor) sex identification based on amelogenin gene - Ming Zhou; Jiaojiao Yu; Rui Xue; Biao Li; Jiandong Yang (Conservation Genetics Resources, 2019)

Cytoprotective Mechanism of the Novel Gastric Peptide BPC157 in Gastrointestinal Tract and Cultured Enteric Neurons and Glial Cells - Xi-Yu Wang; Meihua Qu; Rui Duan; Dengping Shi; Ling Jin; Jinping Gao; Jackie D. Wood; Junhua Li; Guo-Du Wang (Neuroscience Bulletin, 2019)

Complete mitochondrial genome of a kind of snakehead fish Channa siamensis and its phylogenetic consideration - Rui Li; Gang Wang; Zheng-Yong Wen; Yuan-Chao Zou; Chuan-Jie Qin; Yu Luo; Jun Wang; Gui-Hong Chen (Genes & Genomics, 2019)

Multipotential Toxic Metals Accumulated in Urban Soil and Street Dust from Xining City, NW China: Spatial Occurrences, Sources, and Health Risks - Meng Zhang; Xiaoping Li; Rui Yang; Jiwen Wang; Yuwei Ai; Yu Gao; Yuchao Zhang; Xu Zhang; Xiangyang Yan; Bin Liu; Hongtao Yu (Archives of Environmental Contamination and Toxicology, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

A new polyketide purpurogenic acid: the activated production of polyketides by the diethyl sulphate mutagenesis of marine-derived Penicillium purpurogenum G59 - Ming-Wen Xia; Yu Yang; Rui Xu; Chang-Wei Li; Cheng-Bin Cui (Natural Product Research, 2019)

Inhibition of YAP with siRNA prevents cartilage degradation and ameliorates osteoarthritis development - Yong Gong; Song-Jian Li; Rui Liu; Jian-Feng Zhan; Chao Tan; Yi-Fei Fang; Yan Chen; Bo Yu (Journal of Molecular Medicine, 2019)